Experiências de vida e trajetórias dos professores de geografia que nasceram no campo - Artigas, Eliane Liecheski (2019)
The experiences in the field reported through autobiographical narratives are a relevant device to potentialize the study on teacher education in this sense, this qualitative and exploratory research aims to analyze the formation of teachers of basic education geography of the Marechal Cândido Rondon´s city that were born in the field, in order to understand what knowledge is seized in rural space. For which reasons became teachers of geography and how the experiences in the field and the trajectories of schooling are resign field in the exercise of the profession, and helped in theirs professional´s formation. For this, nine teachers of geography participated in this work, who experienced the field in the second half of the twentieth century; Narrate memories experienced in this space from the moment they begin the trajectories of rural schooling educationist. For the study´s development, we opted for the autobiographical methodology, from the perspective of narrative research, using the devices experienced letters and interviews. Finally, the results indicate that the experience in the field contributed to the training and the professional life of teachers and in teaching. The teacher emphasizes through the narratives that the experienced in the structuring of its pedagogical practice, in the way it visualizes the student and seeks through the examples experienced in the field to awaken the interest in geographic knowledge. Therefore, the experiences are reflective artifacts in the teacher´s formation and demonstrate how the experiences in the field contribute to the personal/professional training of the teacher and the exercise of teaching in geography.